Risk factors for dental caries in 5- to 7-year-old Chinese children: a cross-sectional study in Yuyao City - Hu, Geng-Yu; Wang, Wan-Ting; Zhang, Fu-Bo; Zhu, Sen-Yang; Hu, Kong-Fei (Frontiers in Public Health, 2025)
ObjectivePaediatric dental caries, a global public health challenge in developing rural areas, requires targeted interventions due to its links with socioeconomic, dietary, and hygiene factors. This comprehensive investigation aims to identify the risk factors for dental caries among 5- to 7-year-old children in Yuyao City, China, and to highlight the importance of early-life feeding practices in dental health.MethodThis study investigates the risk factors for dental caries in Chinese children aged 5–7 years, providing a comprehensive analysis through a cross-sectional approach in Yuyao City. With a robust sample size of 415 children, the research examines social, dietary and oral hygiene habits to identify both risk and protective factors.ResultThe findings reveal a prevalence of dental caries of 34.2%, with significant risk factors including rural residence, bedtime feeding habits and abnormal salivary pH levels. Notably, mixed feeding during the first 6 months of life is identified as a protective factor.ConclusionThis study contributes to the existing body of knowledge by highlighting the importance of early-life feeding practices in dental health and underscores the need for targeted oral health education in rural areas.